2013
DOI: 10.4102/sajip.v39i1.1070
|View full text |Cite
|
Sign up to set email alerts
|

Biographical and demographical variables as moderators in the prediction of turnover intentions

Abstract: Orientation: The aim of the study was to explore the possible moderation effects of biographical and demographical variables on a prediction model of turnover intention (TI).Research purpose: The main purpose of the study was to determine how biographical and demographical variables have an impact on predictors of turnover intentions.Motivation for the study: Twenty-first century organisations face significant challenges in the management of talent and human capital. One in particular is voluntary employee tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…The finding is however at odds with various studies that found moderating effects of gender in the prediction of the turnover intentions of employees (Cotton & Tuttle 1986;Peltokorpi et al 2015), but is in line with other studies that have failed to find gender to moderate predictors of the turnover intentions, as well as to moderate the relationship between work-life balance and turnover intentions (Du Plooy & Roodt 2013). This finding highlights the contextual relevance of gender as a moderator of these relationships.…”
Section: H1bsupporting
confidence: 75%
See 1 more Smart Citation
“…The finding is however at odds with various studies that found moderating effects of gender in the prediction of the turnover intentions of employees (Cotton & Tuttle 1986;Peltokorpi et al 2015), but is in line with other studies that have failed to find gender to moderate predictors of the turnover intentions, as well as to moderate the relationship between work-life balance and turnover intentions (Du Plooy & Roodt 2013). This finding highlights the contextual relevance of gender as a moderator of these relationships.…”
Section: H1bsupporting
confidence: 75%
“…This result accords with studies that have not found any moderating effects of age in the prediction of turnover intention. For example, age has been found to fail to moderate certain relationships in workplace contexts, such as those between organisational embeddedness and turnover intentions (Peltokorpi, Allen & Froese 2015), but age has been found to moderate relationships predicting turnover intentions (Du Plooy & Roodt 2013;Hellman 1997) in other settings. These findings suggest the importance of context, in that age has a direct and decreasing influence on turnover intentions but does not affect the relationship between WLBC and withdrawal intensions in this setting.…”
Section: Resultsmentioning
confidence: 99%
“…Example items on this scale include 'How often have you considered leaving your current job?' Du Plooy and Roodt (2013) reported a Cronbach's alpha score of 0.80 for their study in the Information and communication Technology sector. Two earlier studies (Jacobs, 2005;Martin, 2007) proved Roodt's (2004) questionnaire to be both reliable (a = 0.913 and a = 0.895, respectively).…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Highly educated employees have been found to be dissatisfied with their jobs due to unfulfilled high expectations and thus were more likely to turnover unlike employees with low levels of education. Other studies have found insignificant relationships between education and turnover intentions or retention (Choong et al, 2013;Du Plooy & Roodt, 2013).…”
Section: Level Of Educationmentioning
confidence: 91%
“…Some studies have found that employees who perform unchallenging, low skill jobs were more likely to stay unlike employees with high status jobs who have better job opportunities. Some studies have found insignificant relationships between job position and turnover intentions (Obwoyere & Kipkebut, 2016;Murupus & Kipkebut, 2015;Du Plooy & Roodt (2013).…”
Section: Job Positionmentioning
confidence: 99%